2017
DOI: 10.5144/0256-4947.2017.232
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of optic atrophy: a prospective observational study from Saudi Arabia

Abstract: BACKGROUNDOptic atrophy (OA) represents permanent retinal ganglion cell loss warranting study to establish etiology.OBJECTIVESTo describe neurogenic causes of OA.DESIGNProspective, observational.SETTINGTertiary care center, Riyadh, Saudi Arabia.PATIENTS AND METHODSWe included consecutive patients of all ages with OA caused by lesions affecting the visual pathways who were referred over a 9-month period (November 2013 to July 2014). Diagnosis was based on visual acuity, ophthalmoscopic features and ancillary te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
9
2
Order By: Relevance
“…Most cases were found as a complication of the proliferative diabetic DR and wet forms of ARMD. In the current study, the commonest cause of OA was glaucoma which is different from Mbekeanis et al (2017) [21], who stated that tumors are the commonest causes of OA in 62.2% of their studied cases, while in the present study, history of tumors was found only in 16% of cases. The general prevalence of vitreous hemorrhage, OA and RD were not reported in the previous literature.…”
Section: Discussioncontrasting
confidence: 96%
“…Most cases were found as a complication of the proliferative diabetic DR and wet forms of ARMD. In the current study, the commonest cause of OA was glaucoma which is different from Mbekeanis et al (2017) [21], who stated that tumors are the commonest causes of OA in 62.2% of their studied cases, while in the present study, history of tumors was found only in 16% of cases. The general prevalence of vitreous hemorrhage, OA and RD were not reported in the previous literature.…”
Section: Discussioncontrasting
confidence: 96%
“…However, we would like to correct a statement that was made in error. In their discussion, Elmorsy and Rehman stated that they found that glaucoma was the most common cause of optic atrophy and that this was contrary to our publication in Annals of Saudi Medicine (2017) [2], which found that optic neuropathy was most frequently secondary to tumors. As authors of the latter paper, we would like to state in the strongest of terms that these two studies were different in purpose, design, patient populations and locations studied and thus are not directly comparable.…”
Section: To the Editorcontrasting
confidence: 60%
“…Lastly, our study was conducted in a specialist referral center in Riyadh whilst the other study was of a free eye camp in the northeastern town of Arar. We concluded that the high frequency of tumors as the cause of optic atrophy likely represented a higher incidence of aggressive tumors coupled with poor recognition/acknowledgement of symptoms and limited access to appropriate centers, resulting in late presentations [2]. We noted that this was different from western populations, where ischemic and neuritis cases predominate as neurogenic causes of optic neuropathy.…”
Section: To the Editormentioning
confidence: 87%
See 1 more Smart Citation
“…Ascending OA develops in acute and chronic vascular impairments, optic nerve inflammation, and central and peripheral retinal degeneration. Identification of the etiology of OA is important in the clinical practice to select the pathogenetic treatment, since management strategy for patients with OA varies depending on the presence of brain neoplasms, demyelination process, intoxication or vascular ocular disorders [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%